Impact of sex and hypoxia on brain region-specific expression of membrane androgen receptor AR45 in rats - Bradshaw, Jessica L.; Wilson, E. Nicole; Mabry, Steve; Shrestha, Pawan; Gardner, Jennifer J.; Cunningham, Rebecca L. (Frontiers in Endocrinology, 2024)
Background Sex differences in oxidative stress-associated cognitive decline are influenced by sex hormone levels. Notably, oxidative stress-associated neuronal cell death can be exacerbated through testosterone signaling via membrane androgen receptor AR45, which is complexed with G protein Gαq within plasma membrane-associated lipid rafts. The objective of this study was to elucidate the impact of sex on the expression of AR45 and Gαq in brain regions associated with cognitive function, specifically hippocampus subregions and entorhinal cortex. Additionally, we investigated whether chronic intermittent hypoxia (CIH), an oxidative stressor with sex-specific effects, would modulate AR45 and Gαq expression in these brain regions. Methods Adult male and female Sprague-Dawley rats were exposed to CIH or normoxia (room air) during their sleep phase for 14 days. We quantified AR45 and Gαq protein expression in various cognition-associated brain regions [dorsal hippocampal CA1, CA3, dentate gyrus (DG), and entorhinal cortex (ETC)] via western blotting. For comparisons, AR45 and Gαq protein expression were also assessed in brain regions outside the hippocampal-ETC circuit [thalamus (TH) and striatum (STR)]. Results The highest AR45 levels were expressed in the hippocampal CA1 and DG while the lowest expression was observed in the extrahippocampal STR. The highest Gαq levels were expressed in the hippocampal-associated ETC while the lowest expression was observed in the extrahippocampal TH. Females expressed higher levels of AR45 in the hippocampal DG compared to males, while no sex differences in Gαq expression were observed regardless of brain region assessed. Moreover, there was no effect of CIH on AR45 or Gαq expression in any of the brain regions examined. AR45 expression was positively correlated with Gαq expression in the CA1, DG, ETC, TH, and STR in a sex-dependent manner. Conclusion Our findings reveal enrichment of AR45 and Gαq protein expression within the hippocampal-ETC circuit, which is vulnerable to oxidative stress and neurodegeneration during cognitive decline. Nonetheless, CIH does not modulate the expression of AR45 or Gαq. Importantly, there are sex differences in AR45 expression and its association with Gαq expression in various brain regions, which may underlie sex-specific differences in cognitive and motor function-associated declines with aging.